Comparative genomics analysis of triatomines reveals common first line and inducible immunity-related genes and the absence of Imd canonical components among hemimetabolous arthropods - Zumaya Estrada, Federico Alonso (2018)
Background: Insects operate complex humoral and cellular immune strategies to fend against invading microorganisms. The majority of these have been characterized in Drosophila and other dipterans. Information on hemipterans, including Triatominae vectors of Chagas disease remains incomplete and fractionated. Results: We identified putative immune-related homologs of three Triatominae vectors of Chagas disease, Triatoma pallidipennis, T. dimidiata and T. infestans (TTTs), using comparative transcriptomics based on established immune response gene references, in conjunction with the predicted proteomes of Rhodnius prolixus, Cimex lecticularis and Acyrthosiphon pisum hemimetabolous. We present a compressive description of the humoral and cellular innate immune components of these TTTs and extend the immune information of other related hemipterans. Key homologs of the constitutive and induced immunity genes were identified in all the studied hemipterans. Conclusions: Our results in the TTTs extend previous observations in other hemipterans lacking several components of the Imd signaling pathway. Comparison with other hexapods, using published data, revealed that the absence of various Imd canonical components is common in several hemimetabolous species.